2018
DOI: 10.1016/j.otsr.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient anterior cervical discectomy: A French study and literature review

Abstract: Cervical spine surgery can be performed in an ambulatory surgery center in carefully selected patients. Our criteria are patients less than 65 years of age, single-level disease, ASA<2, and standard cervical morphology. The complication and readmission rates are low. Careful hemostasis combined with close postoperative monitoring for at least 6hours helps to reduce the risk of neck hematoma. Prevention of postoperative dysphagia must be a focus of the care provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…Postoperative retropharyngeal (RFH), wound (WH), and/or spinal epidural hemorrhages (SEH) following anterior cervical discectomy/fusion (ACDF), anterior corpectomy fusion (ACF), and/ or anterior cervical spine surgery (ACSS) occur in from 0.4%-1.2% of cases. [1][2][3][4][5][6][7][8][9][10][11] e incidence of postoperative hematomas (HT) was culled from 11 articles involving anterior cervical surgery; 4 single case reports, 2 small case series (6 and 30 cases), 4 larger series (758-2375 for a total of 6729 patients), and the largest series of 37,261 ACDF patients from the NSQUIP Database (National Surgical Quality Improvement Program). [1][2][3][4][5][6][7][8][9][10][11] Our aim was to focus on the frequency, symptom duration/recognition, management, and outcomes of postoperative hematomas following cervical spine surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative retropharyngeal (RFH), wound (WH), and/or spinal epidural hemorrhages (SEH) following anterior cervical discectomy/fusion (ACDF), anterior corpectomy fusion (ACF), and/ or anterior cervical spine surgery (ACSS) occur in from 0.4%-1.2% of cases. [1][2][3][4][5][6][7][8][9][10][11] e incidence of postoperative hematomas (HT) was culled from 11 articles involving anterior cervical surgery; 4 single case reports, 2 small case series (6 and 30 cases), 4 larger series (758-2375 for a total of 6729 patients), and the largest series of 37,261 ACDF patients from the NSQUIP Database (National Surgical Quality Improvement Program). [1][2][3][4][5][6][7][8][9][10][11] Our aim was to focus on the frequency, symptom duration/recognition, management, and outcomes of postoperative hematomas following cervical spine surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Early success with this change in practice has moved brain surgery toward an already established process of outpatient procedures in other specialties/subspecialties. [14-16,18,19] Taken together, it has been demonstrated that these measures can reduce hospital stay, thereby reducing the risk of nosocomial infections as well as being cost effective for both the patient and the system.…”
Section: Discussionmentioning
confidence: 99%
“…[28] Early success with this change in practice has moved brain surgery toward an already established process of outpatient procedures in other specialties/subspecialties. [14][15][16]18,19] Taken together, it has been demonstrated that these measures can reduce hospital stay, thereby reducing the risk of nosocomial infections as well as being cost effective for both the patient and the system.…”
Section: Discussionmentioning
confidence: 99%